Community Empowerment Through Koran Guidance and Al-Qur'an Reading and Writing Development at Baabussalam Cidempet TPA - Sri Ayuni; Didik Himmawan (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
Understanding of the Qur'an is the main thing for every Muslim. To gain understanding, the thing that must be owned by a Muslim is the ability to read the Qur'an correctly. Therefore the main thing that must be done is to improve the recitation of the Qur'an. One of the educational efforts in Indonesia is the Al-Qur'an Education Park (TPQ/TPA). Most of the TPQ Baabussalam students are not optimal in pronouncing hijaiyah letters when reading the Qur'an. The large number of students and limited teachers and inadequate learning facilities made activities at TPQ less than optimal, so that TPQ students experienced a lack of knowledge about makhorijul letters. This service uses a method of religious assistance in the form of tutoring in the Koran. The approach method used is the Tutorial and the application of the Baghdadiah Qaidah which was carried out with the TPQ Baabussalam students. This is done because this approach is an effective way for students to listen directly and check understanding and correct the pronunciation of the hijaiyah letters of the TPQ students. With this guidance method students can get closer to partners. The results of this community service activity show that the Koran guidance activity provides a solution to the problems faced by Cidempet Village so that it is able to eradicate Arabic and Al-Qur'an literacy. As well as helping TPQ to improve the quality of reading the Koran for TPQ Baabussalam students.